Correlates Of Use of Family Planning Methods Among Married Women of Reproductive Age Group in Bareilly, India - Khan, Swati; Verma, Rakhee; Mahmood, Syed Esam (National Journal of Community Medicine, 2012)
Background: In India more than 75% of pregnancies are unplanned and a quarter of them are undesired. In spite of availability of many contraceptive techniques, the couple protection rate (41%) continues to be inadequate. Most couples in India do not want to use a contraceptive method on a long-term basis for the fear of side-effects. Hence, unwanted and unplanned pregnancies are quite common. With this background the present study was carried out to assess the pattern of utilization of family planning services provided to married women of reproductive age group in Bareilly. Materials and methods: The cross sectional, community based study involved a survey amongst married women of reproductive age group residing in rural and urban areas of Bareilly district. A structured pretested schedule was used. Chi- square test and ANOVA were used to analyze data. Results: A total of 62.9 % females were currently using family planning methods. A higher proportion of them had undergone sterilization (30.5%) and used condoms (28.2%). The most common reason found for not using any method was lack of awareness (18.3%). 28.7% of females had obtained the family planning method at last use from a private institute. Contraceptive use was significantly higher among the females aged 24 years and above, those who were illiterate, parity 3 or more and belonged to joint families. Conclusion: Only 62.9 % females were currently using family planning methods. Awareness programs regarding the use of family planning methods to avoid unwanted pregnancies need to be strengthened.